Structure of plant community in tropical deciduous forests of Kanyakumari Wildlife Sanctuary, India - SUBASHREE KOTHANDARAMAN; SOMAIAH SUNDARAPANDIAN (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Kothandaraman S, Sundarapandian S.2017. Structure of plant community in tropical deciduous forests of Kanyakumari Wildlife Sanctuary, India. Biodiversitas 18: 391-400. Plantcommunity structure of two tropical deciduous forest sites (I and II which are in different locations with different terrain characteristics viz., elevation and slope pattern) in Kanyakumari Wildlife Sanctuary, Western Ghats were assessed using standard phytosociological methods. Ten plots of 20 m x 20 m each were laid for woody species enumeration and 40 quadrats of 1 m x 1 m (4 in each plot) for understorey vegetation (herbs and plant species that are < 1 m in height) in each site. Overall, 76 plant species were recorded from 41 families, of which 23 contribute to understory. Site I (62) was twice as speciose as site II (31). Greater diversity index of adult woody vegetation was observed in site I (2.30) than site II (2.01). The woody individuals (diameter at breast height, DBH ≥ 10 cm) were more abundant in site I (518 individuals ha-1) than site II (448 individuals ha-1). The basal area of adult trees in sites I and II are 34.7 m2 ha-1 and 30.8 m2 ha-1 respectively. Euphorbiaceae was the most speciose family in both the sites. Twenty-five families in site I and seventeen families in site II were represented by singletons. Diameter class-wise distribution of adult trees showed a typical ‘reverse J-shaped’ curve indicating good regeneration status. Concerning understory, site I (19 species) has a greater diversity than site II (six species). The observed differences in the vegetation patterns between the two deciduous forest sites are possibly due to variations in elevation, terrain features and edaphic characteristics. Keywords: Phytodiversity, species richness, tropical forests, Western Ghats